2010
DOI: 10.1002/pmic.200900506
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the Echinococcus granulosus metacestode during infection of its intermediate host

Abstract: Cystic hydatid disease (CHD) is caused by infection with the Echinococcus granulosus metacestode and affects both humans and livestock. In this work, we performed a proteomic analysis of the E. granulosus metacestode during infection of its intermediate bovine host. Parasite proteins were identified in different metacestode components (94 from protoscolex, 25 from germinal layer and 20 from hydatid cyst fluid), along with host proteins (58) that permeate into the hydatid cyst, providing new insights into host-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 48 publications
4
130
0
1
Order By: Relevance
“…These proteins were reported to contribute to immunoregulatory events at the host-parasite interface during infection. According to the investigators, some of them, such as paramyosin and tetraspanin, may be useful for vaccine development (21).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins were reported to contribute to immunoregulatory events at the host-parasite interface during infection. According to the investigators, some of them, such as paramyosin and tetraspanin, may be useful for vaccine development (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its proliferative activity, the germinal layer is involved in secretory activity and in this respect, Monteiro et al (2010) identified several molecules in hydatid cyst fluid that could play a role in host evasion that presumably were secreted by the germinal layer. Irigoin et al (2001) showed that myo-Inositol hexakisphosphate (IP(6)) which is present in the germinal and laminated layers of E. granulosus inhibits complement activation and Breijo et al (2008) indicated that the establishment and survival of the hydatid cyst is associated with the control of complement and, consequently, of local inflammation.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Only a few papers are devoted to the use of HCF and its partially purified proteins in the diagnosis of CE in camels (Ibrahem et al 2002) and sheep (Simsek and Koroglu 2004, Gatti et al 2007, Jeyathilakan et al 2011. It is known that the presence of large amounts of host proteins in the HCF significantly interferes with identification of the parasite specific proteins (Chemale et al 2003, Monteiro et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, their efficacy in the diagnosis of human hydatid disease remains low (Sarkari and Rezaei 2015). This is due to the presence of large amounts of host pro-teins in HCF reducing the specificity (Chemale et al 2003, Monteiro et al 2010. There is also a lack of standardisation of the target antigen (Sarkari and Rezaei 2015).…”
mentioning
confidence: 99%